Naphthalene as a Cubesat Cold Gas Thruster Propellant - Tsifakis, Dimitrios; Charles, Christine; Boswell, Rod (Frontiers in Physics, 2020)
The `cubesat' form factor (multiples of 10x10x10 cm^3 volume and 1.33 kg mass) has been adopted as the defacto standard for a cost effective and modular, nano-satellite platform. Many commercial options exist for nearly all components required to build such satellite; however, there is a limited range of thruster options that suit the power and size restrictions of a cubesat. This work presents the design, implementation and direct thrust measurements of a proof of concept cubesat cold gas thruster system using naphthalene (C10H8) as the propellant. The proposed design is optimised for simplicity to match the requirement of entry level cubesat missions, yet, due to the properties of naphthalene, it can achieve a total impulse in the order of tens of newton-seconds.